2022
DOI: 10.3389/fpsyg.2022.829083
|View full text |Cite
|
Sign up to set email alerts
|

Faces and Voices Processing in Human and Primate Brains: Rhythmic and Multimodal Mechanisms Underlying the Evolution and Development of Speech

Abstract: While influential works since the 1970s have widely assumed that imitation is an innate skill in both human and non-human primate neonates, recent empirical studies and meta-analyses have challenged this view, indicating other forms of reward-based learning as relevant factors in the development of social behavior. The visual input translation into matching motor output that underlies imitation abilities instead seems to develop along with social interactions and sensorimotor experience during infancy and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 154 publications
0
7
0
Order By: Relevance
“…In the case of humans, evidence has shown that rather than being an exclusively innate ability, imitation capacity develops during infancy and childhood, supported by the maturation of sensorimotor brain networks and domain-general associative learning of multimodal information, both fostered by socially rewarding interactions. This network represents a suitable candidate to coordinate the processing of visual information and the execution of the corresponding motor sequence required for the imitation of facial expressions, such as lip or tongue protrusion (see Michon et al, 2022 ). Accordingly, recent empirical studies and meta-analyses have challenged the widely assumed view that imitation is an innate skill that emerges independent of environmental contingencies, in both human and non-human primate neonates, indicating other forms of reward-based learning as relevant factors in the development of social behavior (see Heyes, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of humans, evidence has shown that rather than being an exclusively innate ability, imitation capacity develops during infancy and childhood, supported by the maturation of sensorimotor brain networks and domain-general associative learning of multimodal information, both fostered by socially rewarding interactions. This network represents a suitable candidate to coordinate the processing of visual information and the execution of the corresponding motor sequence required for the imitation of facial expressions, such as lip or tongue protrusion (see Michon et al, 2022 ). Accordingly, recent empirical studies and meta-analyses have challenged the widely assumed view that imitation is an innate skill that emerges independent of environmental contingencies, in both human and non-human primate neonates, indicating other forms of reward-based learning as relevant factors in the development of social behavior (see Heyes, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent empirical studies and meta-analyses have challenged the widely assumed view that imitation is an innate skill that emerges independent of environmental contingencies, in both human and non-human primate neonates, indicating other forms of reward-based learning as relevant factors in the development of social behavior (see Heyes, 2021 ). Recently, Michon et al, 2022 reviewed empirical studies offering new insights from their understanding of speech as the product of evolution and development of a rhythmic and multimodal organization of sensorimotor information, supporting volitional motor control of the upper vocal tract and audio-visual voices-faces integration, and proposed that human imitation relies on crossmodal associations of sensorimotor information (e.g., visuomotor associations for facial imitation and audiomotor associations for vocal imitation) that develop along with social interactions and sensorimotor experience during infancy and childhood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations